Preparation of oligodeoxyribonucleoside phosphorodithioates by a triester method. - Eldrup, A B (1994)
A method to prepare thymidine phosphorodithioate dimers (ref. 1) has been extended to allow the preparation of oligo-2'-deoxyribonucleotide phosphorodithioates containing all four bases. The method is suitable for large-scale synthesis and gives phosphorodithioates without phosphorothioate impurities (31P nmr, detection limit 0.5 to 1%). Oligonucleotides up to octamers which contain -0-(PS2-)-0- linkages at all positions have been prepared by block synthesis in solution. The phosphorodithioate linkage is introduced by the reaction of a 5'-O, N-protected nucleoside (or oligonucleotide) with a dithiophosphorylating agent RSP(S)(ODhbt)2, R = 2,4-dichlorobenzyl, Dhbt = 3,4-dihydro-4-oxo-benzotriazin-3-yl, followed by coupling of the product to a 3'-O,N-protected nucleoside (or oligonucleotide). This method gives pure protected oligodeoxyribonucleoside phosphorodithioates, and phosphorothioate linkages are only introduced if contact with conc. aqueous ammonia during or after deblocking is unduly prolonged.